2011
DOI: 10.1152/ajpheart.01169.2010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vascular responses of insulin-resistant rats after mild subarachnoid hemorrhage

Abstract: DW. Impaired vascular responses of insulinresistant rats after mild subarachnoid hemorrhage. Am J Physiol Heart Circ Physiol 300: H2080 -H2087, 2011. First published March 18, 2011 doi:10.1152/ajpheart.01169.2010.-Insulin resistance (IR) impairs cerebrovascular responses to several stimuli in Zucker obese (ZO) rats. However, cerebral artery responses after subarachnoid hemorrhage (SAH) have not been described in IR. We hypothesized that IR worsens vascular reactions after a mild SAH. Hemolyzed blood (300 l) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…NMDA‐induced neuronal NO release and vasodilation seem to be an astroglia and endothelium‐independent process , and it presumably activates K ATP channels and K Ca channels on the vascular smooth muscle surface . Our earlier experiments on the basilar artery in vivo and on the isolated middle cerebral artery clearly showed that K Ca ‐ and K ATP ‐channel‐mediated dilations are significantly reduced in fructose‐fed IR rats as well as in ZO rats . Importantly, these vascular dysfunctions were reversed with antioxidant enzymes and protein kinase C antagonists .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…NMDA‐induced neuronal NO release and vasodilation seem to be an astroglia and endothelium‐independent process , and it presumably activates K ATP channels and K Ca channels on the vascular smooth muscle surface . Our earlier experiments on the basilar artery in vivo and on the isolated middle cerebral artery clearly showed that K Ca ‐ and K ATP ‐channel‐mediated dilations are significantly reduced in fructose‐fed IR rats as well as in ZO rats . Importantly, these vascular dysfunctions were reversed with antioxidant enzymes and protein kinase C antagonists .…”
Section: Discussionmentioning
confidence: 86%
“…The abnormal reactivity of main cerebral vessels is worsened in the 17‐week‐old diabetic ZO rat . The observed vascular dysfunction of the cerebral arteries probably contributes to the higher vulnerability of ZO animals to both ischemic and hemorrhagic stroke . Despite the thorough investigation of IR‐induced dysfunction of the major cerebral arteries, little is known about the effect of IR on microvascular reactivity at the level of the local cortical microcirculation in both pre‐diabetic and diabetic stages.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelium-dependent relaxation responses to Ach have been previously found to be reduced in mesenteric arteries of 15-to 18-week-old OZR (Romanko and Stepp 2005;Vessières et al 2010), in brain arteries of 11-to 13-week-old OZR (Institoris et al 2011), and in penile arteries of 17-to 18-week-old OZR (Villalba et al 2009). Responses to Ach were also slightly impaired in coronary arteries from 12-to 18-week-old OZR (Picchi et al 2006;Sánchez et al 2010), but were not affected in coronary arteries of 17-to 18-week-old OZR (Villalba et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…This animal model shows dramatically different and often opposite responses depending on the type of vessels studied and the different age stages, and results are often inconsistent between studies (Auguet et al 1989;Institoris et al 2011;Moral-Sanz et al 2011;Oltman et al 2006;Picchi et al 2006;Romanko and Stepp 2005;Sánchez et al 2010;Subramanian and MacLeod 2003;Vessières et al 2010;Villalba et al 2009). At least in the aortic vessel, most data point to exaggerated endothelium-dependent vasodilator responses and impaired vasoconstrictor responses, although the contribution of endothelium-derived relaxing and constricting factors, including NO and prostanoids, has not been fully elucidated (Auguet et al 1989;Oltman et al 2006;Subramanian and MacLeod 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported the use of adjuvants to promote the occurrence of ischemia. The first study published in 2011 described a direct injection model in insulin-resistant rats (64).…”
Section: Characteristics Of Sah Models In Rats and Micementioning
confidence: 99%